Phytochemical Analysis and Antimicrobial Properties of Eugenia caryophyllata (Syzigium aromaticum L. Myrtaceae) (Journal of Environmental Bioremediation and Toxicology, 2021)
This study is aimed at analyzing the phytochemicals and elucidating the antimicrobial properties of Syzygium aromaticum (Clove) which is one of the most popular and widely used spice that has been reported to possess high nutritional value, antimicrobial properties. 100% aqueous and 20:80% (water and alcohol) for hydroethanolic and hydromethanolic extracts were prepared. About 13 phytochemical compounds were detected qualitatively in all of the three different extracts which include phenolic compounds, tannins, ascorbic acid e.t.c. Sensitivity disc method was used to test the antibacterial and antifungal properties of Syzygium aromaticum (clove) was found that all pathogenic bacteria and fungus were inhibited by the Clove. Staphylococcus aureus was more sensitive with greater zone of inhibition of (12.33Â±0.88 mm) than the other bacteria. Candida albicans had no activity at concentration of 0.25 mg/mL in comparison with standard antibiotic (amoxicillin). The clove methanolic extract produced same zones of inhibition with amoxicillin (12.33Â±1.20 mm), which was used as a control and minimum inhibitory concentration was found to be 0.25 mg/mL for both gram positive and Gram-negative bacteria, respectively, and 0.5 mg/mL for Candida albicans.
Keywords: Clove; Phytochemical; Antimicrobial; Staphylococcus aureus